Pilgrims in Old Uyghur Inscriptions: A Glimpse behind Their Records - Raschmann, Simone-Christiane (Dynamics in the history of religions, 2020)
When dealing with the subject of pilgrimage in Old Uyghur manuscripts, we encounter a lack of detailed personal reports like those of the famous Chinese pilgrims Xuanzang, Faxian or Yijing. On the other hand, a huge amount of Old Uyghur Buddhist scriptures of varying content, as well as records of Buddhist communities and monasteries, are preserved and clearly demonstrate the widespread and fairly long-lasting Buddhist orientation of the Uyghurs. Since pilgrimage is an important Buddhist practice, it is worth looking for traces of pilgrims in the remains of Old Uyghur inscriptions to find out their story. Old Uyghur pilgrim inscriptions discovered in the Hexi and Turfan regions are the focus of this chapter. By using the results of a multi-disciplinary research project of ruin Q in Kočo, the significance of this site as a ‘holy place’ for Buddhist pilgrims is revealed.